Achieving the qualities of the meanings part of «The footnote of Ibrahim bin Muhammad bin Arab Shah Al-Esfraini, famous for: Essam Al-Din (T .: 951 AH) on the explanation of Al-Nasif’s beliefs».From paper (66 / back) to paper (71 / back) - Mahmoud, Ahmed Shaker (Journal of Tikrit University for Humanities, 2022)
This research investigates a canonical text that has scientific and historical value, for one of the Islamic scholars who lived from the beginning of the second half of the ninth century until the middle of the tenth century AH, and that is Sheikh Ibrahim bin Muhammad bin Arab Shah Al-Esafraini, known as: Essam Al-Din (d. : 951 AH)This text is part of his “commentary on the explanation of al-Nasif’s beliefs,” one of the books approved by Ahl al-Sunnah wal-Jama` in the field of theology.Sheikh Essam El-Din was famous for being a meticulous owner, and he had follow-ups and conclusions on his predecessors, as he is a scholar not traditional.This text includes the thoughts and perspectives of Sheikh Essam El-Din, which he wrote in the form of comments on explaining the Nasfi beliefs, and what our concern is is the section on two matters: Proving that the divine attributes (meanings) must be said that they exist. It must be said that it is in addition to the divine self so that the understanding and knowledge of the divine self and its characteristics are organized in a manner that is definitely consistent with the nature of human thinking based on the law of Islam. So the researcher made a short translation, copied the text, met it in five handwritten copies, and took care of it as an investigation into the margin.